Evaluation Study of the Green School Program in Islamic Schools - Wahjusaputri, Sintha; Suwardi, Suwardi; Nazhif, Fikri Adli (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This research aims to evaluate the effectiveness of the Green School Program in enhancing student character education at Adzkia Islamic School Boarding School in South Tangerang City. Employing a qualitative approach with a case study design, the study adopts the Context, Input, Process, Product (CIPP) evaluation model. The research involved 10 informants, including the principal, teachers, dormitory caretakers, and high school students. Data were collected through structured interviews, observations, and documentation, and analysed using Miles and Huberman’s interactive model. The findings indicate that while the Green School and character education programs are being effectively implemented, several areas require improvement, such as the availability of environmental infrastructure, curriculum integration, individual-level evaluations, and reporting mechanisms. Theoretically, this study supports the role of environmentally-based education in shaping student character. Practically, it provides insights for school administrators and policymakers to enhance sustainable character education through comprehensive planning and infrastructure. Future research is recommended to develop assessment instruments and explore program impacts quantitatively across different school levels.